The Syrian Refugee Life Study : First Glance - Miguel, Edward A.; Palmer, Bailey; Rozo Villarraga, Sandra Viviana; Stillman, Sarah Virginia; Smith, Emma; Tamim, Abdulrazzak (Washington, DC: World Bank, 2022)
This paper presents descriptive statistics from the first wave of the Syrian Refugee Life Study (S-RLS), which was launched in 2020. S-RLS is a longitudinal study that tracks a representative sample of 2,500 registered Syrian refugee households in Jordan. It collects comprehensive data on socio-demographic variables as well as information on health and well-being, preferences, social capital, attitudes, and safety and crime perceptions. This study uses these novel data to document the socio-demographic characteristics of Syrian refugees in Jordan, and compare them to those of the representative Jordanian and non-Jordanian populations interviewed in the 2016 Jordan Labor Market Panel Survey. The findings point to lags in basic service access, housing quality, and educational attainment for the Syrian refugee population, relative to the non-refugee population. The impacts of the pandemic may serve to partially explain these documented disparities. The data also illustrate that most Syrian refugees have not recovered economically from the shock of COVID-19 and that this population has larger gender disparities in terms of income, employment, prevalence of child marriage, and gender attitudes than their non-refugee counterparts. Finally, mental health problems are common for Syrian refugees in 2020, with depression indicated among over 61 percent of the population.